The earthquake intervent time distribution along the Hellenic subduction Zone. - Papadakis, G.; Vallianatos, F.; Michas, G. (Bulletin of the Geological Society of Greece, 2013)
The Hellenic Subduction Zone (HSZ) is the most seismically active region in Europe (Becker and Meier, 2010). The evolution of such an active region is characterized by complex phenomenology and is expressed through seismicity. Seismicity temporal patterns remain as one of the most important topics in earth sciences. The Weibull distribution has been used as a recurrence time model for large earthquakes (Rikitake, 1976; Rikitake, 1991). Moreover,Hasumi et al. (2009) used the Weibulllog Weibull distribution for the study of the interoccurrence times of earthquakes in Japan.The dataset formed in this study concerns the seismic belt of the HSZ during the period 1976-2009. We use the external seismic sources of shallow earthquakes in the Aegean and the surrounding area (Papaioannou and Papazachos, 2000) along with the updated and extended earthquake catalogue for Greece and adjacent areas (Makropoulos et al., 2012).The application of the Weibull distribution to the interevent times of the formed dataset is analyzed and discussed.